Estasi e frammentazione dell’io nella governamentalità algoritmica - Specchio, Valerio (Mechane, 2025)
This paper explores the relationship between technology and power within the framework of algorithmic governamentality, with a particular focus on the fragmented and ecstatic condition of the user. The hypothesis of the paper suggests that, within algorithmic governamentality, the fragmented-ecstastic condition of the user is used as raw material that fuels the directly proportional relationship between the consumption of user’s transparency and the development of algorithmic opacity in platform society. The paper starts by exploring the relationship between invisibility and opacity in algorithmic governamentality then draws points of contact between: a) the work of Erik Davis on techngnostic philosophies in the informationa age; b) Jean Baudrillard’s concept of the ecstasy of communication; c) Bernard Stiegler’s thoughts on the industry of trace and proletarianization of minds in the automatic society.